Interest in Telehealth Among Patients With Chronic Retinal Conditions. (September 2021) - Karthik, Naveen; Shields, Ryan A.; Brown, Meghan M.; Aoun, Mariam; Wolfe, Jeremy D.; Drenser, Kimberly A.; Capone, Antonio; Williams, George A.
Purpose: This work investigated interest in telehealth services for patients with chronic retinal conditions. Methods: A single-center, multi-office study was conducted of patients with chronic retinal conditions who were seen by 1 of 4 physicians during June 2020. Patients whose next appointment was 6 months or later were telephoned. Patients completed a phone interest survey about their interest in a hybrid telehealth evaluation instead of a complete office evaluation with their provider. Results: Of 2136 patients reviewed, 453 met eligibility to participate in the survey. A total of 159 patients (35.1%) participated, of whom 91 (57.2%) indicated an interest in telehealth at their next follow-up visit. Of the 68 (42.8%) patients without a current interest in telehealth, 13 (19.1%) expressed interest in pursuing telehealth in the future. Age ( P = .19), sex ( P = .22), race ( P = .79), office location ( P = .19), number of prior visits ( P = .58), and median household income by patient's zip code ( P = .14) were not predictors of telehealth interest. Among diagnoses, dry age-related macular degeneration was associated ( P = .04) with increased interest in telehealth. An increased number of ocular diagnoses were also found to predict a decreased ( P = .04) interest in telehealth. multivariable analysis revealed healthcare provider as the only significant predictor for interest in telehealth ( P = .03). Conclusions: Most patients with chronic retinal conditions may be interested in incorporating telehealth into routine care. Considerations should be made to evaluate interest in telehealth to guide patients to clinical experiences that best suit their needs.